2011
DOI: 10.1007/s00590-011-0849-z
|View full text |Cite
|
Sign up to set email alerts
|

Monomicrobial necrotizing fasciitis caused by coagulase-negative Staphylococci and methicillin-resistant Staphylococcus aureus

Abstract: Background Coagulase-negative staphylococci (CoNS)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
(52 reference statements)
1
1
0
Order By: Relevance
“…Similar to the present case, lower limb skin lesions and underlying diabetes mellitus were common associations in eight and nine patients, respectively. 15 Sato et al also isolated CoNS in a case of NF from right lower extremity, similar to our case. 16…”
Section: Pathogenesis Of Necrotizing Fasciitis and Coagulase-negative...supporting
confidence: 88%
See 1 more Smart Citation
“…Similar to the present case, lower limb skin lesions and underlying diabetes mellitus were common associations in eight and nine patients, respectively. 15 Sato et al also isolated CoNS in a case of NF from right lower extremity, similar to our case. 16…”
Section: Pathogenesis Of Necrotizing Fasciitis and Coagulase-negative...supporting
confidence: 88%
“…14 Clinically significant in immunocompromised individuals. 15 Shen et al described NF with CoNS, an aerobic, gram-positive coccus commonly found on human skin, increasingly recognized as a role in bacteremia. They isolated CoNS in 11 patients.…”
Section: Pathogenesis Of Necrotizing Fasciitis and Coagulase-negative...mentioning
confidence: 99%